Microstructure stability of γ-TiAl produced by selective laser melting. (15th March 2017) - Gussone, J.; Garces, G.; Haubrich, J.; Stark, A.; Hagedorn, Y.-C.; Schell, N.; Requena, G.
Abstract: The effects of intrinsic heat-treatment during selective laser melting of Ti-44.8Al-6Nb-1.0Mo-0.1B are studied and compared to extrinsic post-annealing. Phase evolution during heat-treatment of as-built samples studied by in situ synchrotron radiation diffraction showed pronounced intensity changes and peak shifts below the eutectoid temperature, which are explained by stabilization of α2 as well as transformations to γ and β/βο . These observations contrast the marginal intensity changes found for the microstructure thermodynamically stabilized by hot isostatic pressing. The intrinsic heat-treatment of the as-built state leads to graded microstructures characterized by an increase of globular γ and β/βο at the α2 /γ colony boundaries. Graphical abstract: